Mullers Muscle Conjunctival Resection for Treatment of Contact Lens-Associated Ptosis. Issue 4 (July 2016) - Teo, Livia; Lagler, Christine P.; Mannor, Geva; Glass, Lora D.; Freitag, Suzanne K.
Abstract : Purpose: The aim of this study was to look at the surgical outcomes of posterior approach Mullers muscle conjunctival resection surgery for contact lens-related ptosis. Methods: This was a retrospective, comparative interventional case series. All patients and controls underwent phenylephrine 10% testing and had a positive response prior to surgical intervention. Results: Thirty-one eyelids with ptosis were identified in 20 contact lens wearing patients, which were matched with 27 eyelids in 15 controls. The contact lens wearing patients wore contact lenses for a mean of 20.6 ± 12.1 years. More than half (60%) wore soft contact lenses, as opposed to rigid gas-permeable contact lenses. Preoperative margin-to-reflex distance-1 was lower in patients who wore rigid contact lenses (0.8 ± 0.7 mm) as compared with patients with soft contact lenses (1.7 ± 1.1 mm) ( p = 0.01). Surgical success, as defined by margin-to-reflex distance-1 ≥3 mm or symmetry of upper eyelid height (within 1 mm), was achieved in 93.5% in the contact lens group and 92.6% of controls. Postoperative margin-to-reflex distance-1 was significantly higher in the contact lens wearers (3.9 ± 1.3 mm) compared with the controls (3.2 ± 1.1 mm; p = 0.01). There was a significant correlation between the amount of tissue resected intraoperatively and the improvement in margin-to-reflex distance-1 (Pearsons correlation coefficient, r =0.36; p = 0.006). There were no surgical complications of any patients in the study. Conclusion: Mullers muscle conjunctival resection surgery is an effective surgical correction for contact lens-associated ptosis. Patients can achieve excellent results with minimal risk of residual ptosis or asymmetry. Abstract : Patients can achieve excellent surgical correction of contact lens associated ptosis with Mullers Muscle Conjunctival Resection surgery with minimal risk of residual ptosis or asymmetry.